Lifestyle Impact on the State of Emotional Balance among Medicine University Students. A Questionnaire Bases Study - Nemes, Mara; Niculici, Ioana-Maria; Stoica, Alexandra Mihaela; Nyulas, Ancuta Victoria (European Scientific Journal, ESJ, 2023)
Objectives: This article analyzes the emotional balance of the student with such an important role in his life as well as the link between lifestyle and the conscious, independent choices that can influence this balance. Our study was conducted among the students who study at the Faculty of General Medicine, UMFST G.E. Palade from Targu Mures, Romania. Material and methods: We conducted an anonymous survey using a questionnaire that included 21 questions. All the 132 participants from all medicine specialties studying at Faculty of General Medicine from Targu-Mures. The completed questionnaires were collected and the results were evaluated and statistically analyzed using chi-square test. Results: Most students have a chaotic lifestyle during their university years. Only 71 (54%) of the students say they have a healthy diet, 46% (61) use to eat fast food once a week, 64% (85) claim to sleep less than 8 hours a day, 30% are smokers and 62% have tried smoking marijuana. On the other side, based on the questions that concerned the emotional balance, most students, 65% consider to be stressed during the university period and only 14% are willing for Monday to come in order to start doing their usual activities. Conclusions: A healthy lifestyle can give us good emotional health, which helps us to effectively manage stress, to improve relationships with those around us, giving us the opportunity to connect better with others, to express our empathy and compassion in the life situations we are exposed to.